DETERMINATION OF SERUM MACRONUTRIENT ELEMENTS (SODIUM, POTASSIUM, CHLORIDE AND SULFATE) AND MICRONUTRIENT ELEMENTS (COPPER, AND SILICON) FOR WOMEN OSTEOPOROSIS - Al-Khaqani, Manal F. (International Journal of Psychosocial Rehabilitation, 2020)
In this study clarification to evaluate serum macronutrient elements including potassium, sodium, chloride, and sulfate, also some micronutrient elements including copper, and silicon in patients and; they were compared with the control group. The disease was diagnosed by Dual-energy X-ray absorptiometry for women aged 50-75 years, the incidence of the disease was determined by an indicator by T-scores.The value of potassium and other elements was measured for the (65) patients and (35) healthy patients diagnosed by radiation. Results were compared between patients and healthy women and the correlation coefficient was calculated for some parameters.The results demonstrated significantly higher values of chloride, sulfate, and copper in the serum of osteoporosis women when compared to women (healthy). T-scores were significantly decreased in osteoporosis group women, compared to control groups.Serum copper, chloride and sulfate are high for women with osteoporosis and there is a significant relationship when compared to the control group. There was no significant difference for serum sodium, silicon, and potassium measured for both groups; And was used to diagnose fragility according to the data of the scale T-scores from the scan.